Regulatory mechanisms of HMGB1 and its receptors in polycystic ovary syndrome‐driven gravid uterine inflammation. (8th December 2022) - Hu, Min; Zhang, Yuehui; Lu, Yaxing; Han, Jing; Guo, Tingting; Cui, Peng; Brännström, Mats; Shao, Linus R.; Billig, Håkan
Abstract : High‐mobility group box 1 (HMGB1) is critical for inflammatory homeostasis and successful pregnancy, and there is a strong association among elevated levels of HMGB1, polycystic ovary syndrome (PCOS), chronic inflammation and pregnancy loss. However, the mechanisms responsible for PCOS‐driven regulation of uterine HMGB1 and its candidate receptors [toll‐like receptor (TLR) 2 and 4] and inflammatory responses during pregnancy remain unclear. In this study, we found a gestational stage‐dependent decrease in uterine HMGB1 and TLR4 protein abundance in rats during normal pregnancy. We demonstrated that increased expression of HMGB1, TLR2 and TLR4 proteins was associated with activation of inflammation‐related signalling pathways in the gravid uterus exposed to 5α‐dihydrotestosterone and insulin, mimicking the clinical features (hyperandrogenism and insulin resistance) of PCOS and this elevation was completely inhibited by treatment with the androgen receptor (AR) antagonist flutamide. Interestingly, acute exposure to lipopolysaccharide suppressed HMGB1, TLR4 and inflammation‐related protein abundance but did not affect androgen levels or AR expression in the gravid uterus with viable fetuses. Furthermore, immunohistochemical analysis revealed that, in addition to being localized predominately in the nuclear compartment, HMGB1 immunoreactivity was also detected in the cytoplasm in the PCOS‐like rat uterus, PCOS endometrium and pregnant rat uterus with haemorrhagic and resorbed fetuses, possibly via activation of nuclear factor κB signalling. These results suggest that both AR‐dependent and AR‐independent mechanisms contribute to the modulation of HMGB1/TLR2/TLR4‐mediated uterine inflammation. We propose that the elevation of HMGB1 and its receptors and disruption of the pro‐/anti‐inflammatory balance in the gravid uterus may participate in the pathophysiology of PCOS‐associated pregnancy loss. Abstract : Our study comprehensively profiles the gestational stage‐dependent regulation of HMGB1/TLR2/TLR4 proteins in the gravid uterus. Using an AR‐specific agonist and antagonist as well as the LPS‐induced fetal loss model in this study, we propose that the aberrant regulation of uterine HMGB1, TLR2 and TLR4 proteins contributes to aberrant inflammation‐induced implantation defects and fetal loss during pregnancy through both AR‐dependent and AR‐independent mechanisms.